Inhibition of In Vitro Clot Growth by r-Hirudin Is More Effective and Longer Sustained than by an Analogous Peptide - Römisch, Jürgen; Stöhr, Hans-Arnold; Stauß, Harald; Koschinsky, Rainer; Stüber, Werner; Pâques, Eric-Paul (Thrombosis and Haemostasis, 1994)
The specific thrombin inhibitors r-hirudin and a synthetic peptide (I) D-FPRP(G)4-NGDFEEIPEEYL were compared in in vitro tests, r-hirudin proved to be the superior compound with respect to inhibition of amidolytic small substrate turnover that is catalysed by soluble and immobilised thrombin as well as to inhibition of fibrinogen activation. In an in vitro clot model significantly higher molar concentrations of peptide I are needed to achieve fibrin bound thrombin inhibition equivalent to that of r-hirudin. Stable complexes consisting of thrombin and hirudin oppose labile complexes containing the synthetic peptide. The latter leads to a regaining of thrombin activity with subsequent additional fibrin accretion. Analyses of the mixtures of thrombin and peptide I display a time dependent release of amino-terminal D-FPR peptide (III) exhibiting, similar to the residual fragment (peptide II), only weak inhibitory activity. Peptide I and the carboxy-terminal fragment induce, within a certain concentration range, an increase in thrombin activity and clot growth.